Rheumatological emergencies – Perspective of an intensivist - Paudel, Ashmita; Bhandari, Sabin; Jha, Saket; Pradhan, Bijay (Journal of Nepalese Society of Critical Care Medicine, 2023)
Rheumatological disorders include a diverse range of disorders characterized by chronic inflammation and autoimmunity. Rheumatoid arthritis, systemic lupus erythematosus (SLE), scleroderma, antineutrophilic cytoplasmic antibody (ANCA) associated vasculitis are some common conditions that present to the intensive care unit (ICU). Emergencies due to these rheumatological disorders can present in different forms. Multiple organ system involvement in critically ill patients may be due to various conditions which creates a diagnostic dilemma. Prompt identification and management of devastating complications of the disease itself or associated therapeutics are of great challenges for critical care physicians. Early detection of disease-specific complications, and patient-tailored therapeutic interventions are crucial for optimal patient outcomes. Collaboration between rheumatologists, intensivists, and other relevant professionals is paramount in the management of rheumatological emergencies in ICU. This review focuses on common rheumatological emergencies that are encountered in ICU.